Who benefits from energy policy incentives? The case of jatropha adoption by smallholders in Mexico. (April 2015) - Soto, Iria; Achten, Wouter M.J.; Muys, Bart; Mathijs, Erik
Abstract: Understanding the distribution of policy incentives is important in evaluating the impact of promotion programmes. This study investigates the allocation of economic subsidies to jatropha cultivation by using adoption models at both the community and household levels in Chiapas. At the community level, we compared socioeconomic and environmental variables of the communities that adopted jatropha to non-adopters. At the household level, 420 farm households were surveyed to analyse both the determinants of adoption and the extent of adoption (i.e. hectares dedicated to jatropha). The variables determining adoption were analysed at both levels using generalised linear models. The extent of jatropha adoption was assessed using ordinary least squares multiple regression. Quantitative data was complemented with key stakeholder interviews and focus groups. Results show that subsidies tend to be allocated to larger, better-connected communities which have access to better services. Within adopter communities, the subsidy is distributed among households that have more resources, better risk-coping strategies, better access to information, more experience with similar technologies and whose attitude towards risk is positive. This study provides lessons that can be useful for the introduction of new energy crops to better reach the target group and ultimately achieve the aims of energy promotion strategies. Highlights: We examine the allocation of subsidies for bio-energy crop cultivation. We used a multilevel and multi-approach technique to model adoption. Extension, community and households features influence subsidy distribution. Poor and marginalised farmers tend to be excluded from the subsidy. We provide tools to assess if subsidies reach targeted population.